Genetic Diversity Within and Among Populations of Shorea Robusta Roxb. Ex Gaertn. In Bangladesh and Its Implications for Conservation (Bangladesh Journal of Botany, 2021)
Fragmentation and reduction of natural population size render threats to the conservation of forest resources through depletion of genetic diversity. Hence, information on genetic structure of Sal (Shorea robusta Roxb. ex Gaertn.) populations is relevant for proper management and conservation of the tropical deciduous forests. The present study focused on assessing the genetic diversity of the populations of Sal which was the dominant tree species of the deciduous forests of Bangladesh. Plant leaf samples were collected from the three populations of Sal distributed in the three geographical regions including Madhupur tract in the districts Tangail and Gazipur and that of the districts of Cumilla and Dinajpur. DNA band profiles were generated using eight ISSR primers for a total of 13 samples taken from the three populations. Statistical analysis was done using PopGen 32 and GenAlEx 6.5 softwares. Principal coordinate analysis done on the DNA band profiles revealed that Sal populations of Madhupur tract and Cumilla positioned nearby while Dinajpur showed maximum genetic distance with that of Cumilla. Mantel test showed significant (p=0.05) correlation between genetic and geographic distances indicating “Isolation by Distance”. Data of the present study indicated higher genetic polymorphism (68.87%) in the Sal population of Madhupur tract compared to other two populations. Small population size of Sal of Dinajpur forest might be related with its low genetic diversity. Data of the present study suggest immediate attention for the conservation of Sal forests in Bangladesh before further genetic erosion occurs.Bangladesh J. Bot. 50(2): 405-412, 2021 (June)